The Relationship of the Work Environment, Use of Masks and Length of Exposure to Smoke with the Incident of ISPA in Melinjo Emping Craftsman - Zaharamutia, Zaharamutia; Zahara, Meutia; Nurjannah, Nurjannah; Maifrizal, Maifrizal (Indonesian Journal of Global Health Research, 2024)
Melinjo cracker home industry workers must pay attention to several factors that can cause ISPA incidents, such as using personal protective equipment by wearing a mask because it can protect their breathing from dust and smoke resulting from heating melinjo fruit. The purpose of this study is to determine the relationship between the work environment, mask use and the duration of smoke exposure to the incidence of ispa in emping melinjo artisans in Kembang Tanjong District, Pidie Regency in 2023. Workers must also pay attention to the length of work each day, at least taking time to rest. This type of research is descriptive-analytic using a cross-sectional design. The sample taken in this research was the entire population in the Kembang Tanjong sub-district, 435 people who were emping melinjo craftsmen in the Kembang Tanjong sub-district, Pidie Regency. Data analysis in this study was univariate, bivariate, and multivariate. The results of the research show that there are three variables that have a relationship with the incidence of ISPA in emping melinjo craftsmen, namely: Length of exposure to smoke, p-value 0.000, use of masks, p-value 0.000, working place conditions, p-value 0.035 and roof condition, p-value 0.000, while for Multivariate test of risk factors The most associated with the incidence of ISPA is the use of masks with a p-value of 0.000, length of exposure to smoke p-value of 0.000 and roof condition p-value of 0.004.